Comparing the DUALEM and VÉRIS sensors for mapping soil properties - Serrano, João (2014)
The objective of this study was to evaluate two apparent soil electrical conductivity (ECa) sensors (DUALEM 1S and VERIS 3100) for mapping soil property variability in a Mediterranean shallow soil. The ECa data from the top 0-0.30 m soil layer were used. Soil spatial variability of a 6ha experimental field was characterized by 76 samples geo-referenced with GPS. The results of the DUALEM sensor showed significant correlation coefficients between ECa and the relative field elevation (RFE), bedrock depth, pH, sand, silt and soil moisture content. On the other hand, significant correlation coefficients were found between the ECa measured by VÉRIS sensor and pH, sand, clay, organic matter and soil moisture content. This paper discusses possible reasons for the somewhat different behaviour of the two sensors.